Language and Intercultural Communication: Belgian Business Owner with Indonesian Workers in Murianto Workshop, Jepara, Central Java - Ulfani, Kireina Geza; Handayani, Andri (DBSMB, Vocational College of Universitas Gadjah Mada, 2024)
This study explores the dynamics of intercultural communication between Niels Evens, a Belgian business owner, and his Indonesian workers in the Murianto Workshop in Jepara, Central Java. Drawing upon the Communication Accommodation Theory (CAT) by Giles and Coupland and the Conversational Constraints Theory (CCT) by Kim, the study discusses the interplay of cultural adaptation and communication strategies. The objectives of this study are to understand the implementation of CAT and CCT by the owner and the workers of Murianto Workshop in Jepara, Central Java, and also to identify the constraints during the communication between the owner and the workers of Murianto Workshop. The data for this research was gathered through a semi-structured interview conducted with Niels Evens and presented descriptively. The finding shows that Niels Evens’ effort to adapt and understand the local culture can be called convergence from the Communication Accommodation Theory. Although many of his actions reflect collectivist tendencies, he establishes boundaries with his workers to maintain a professional work environment. From the Conversational Constraints Theory, it can be concluded that the constraints faced by Niels Evens are about clarity and effectiveness concerns. The constraints he faced are related to the change of communication strategy from a direct to an indirect approach, which is also his constraint in adapting to the local culture.